Information Technology Governance Capability at PT XYZ using COBIT 2019 - Kurniawan, Jesslyn; Wella, Wella (Universitas Multimedia Nusantara, 2023)
PT XYZ is a management consulting company in Jakarta. This company has many products related to information technology. Therefore, measuring the capability of information technology governance at PT XYZ was carried out. The measurement of information technology governance capability is based on problems that are often faced by companies in terms of project management followed by problems related to the company's IT budget and human resources skilled in information technology. Capability measurement is carried out using COBIT 2019 with a qualitative approach. Using data collection methods with interviews and literature study. The results of the data collection showed that there were 3 COBIT 2019 domain processes that matched the company's problems, namely APO06 - Managed Budget and Costs, APO07 - Managed Human Resources, and BAI11 - Managed Projects. The results of the capability measurement carried out concluded that the three selected domain processes namely APO06, APO07, and BAI11 were achieved at level 2 or can be categorized as Fully Achieved so that companies get several recommendations for improvement to improve the quality of their information technology governance and reach a higher level.